Analisis Tayangan Indonesia Lawyers Club di TV One bagi Pemahaman Politik - Anisah Ulfi; Prayetno Prayetno (Universitas Negeri Medan, 2018)
The aim of this research is to find out the understanding of the political community after watching the Episode